Interpreting materia medica. A case study on Ioannes Archiatrus [version 2; peer review: 2 approved, 1 approved with reservations] - Andreas Lardos; Barbara Zipser; Robert Allkin; Rebecca Lazarou; Andrew C. Scott; Mark Nesbitt (Wellcome Open Research, 2024)
Background Premodern medical texts are an invaluable source for scholars from humanities and sciences. However, they are usually not accessible as few scientists with an interest in premodern materia medica are also qualiﬁed philologists. Therefore, a balance has to be struck to translate these texts while preserving information on how reliable we believe a given translation to be. In this paper, we conduct a case study on the vernacular version of Ioannes archiatrus. Methods The present study forms part of the output of a multidisciplinary Wellcome Trust Collaborative Award combining humanities and sciences. We deployed a multi-layer tagging system to systematise pharmaceutical terminology and to translate these terms while providing conﬁdence factors for individual words. In a second step, we used AntConc, a freeware concordance software, to analyse our primary source and visualise patterns in the text. Results Our methodology created a readable text that made it possible for the reader to check conﬁdence factors. It also allows our translation and tagging to be recycled for further research. Conclusions Our methods provide a tool that allows to balance the need to translate and the necessary caution about translated plant and mineral names. Our approach is transferable and it can be modiﬁed to suit the needs of other primary sources.